COVID-19 and online distance learning in Malaysia: A blessing or a curse? - Kamaludin, Kamilah; Sundarasen, Sheela (Frontiers in Education, 2023)
This study intends to investigate the extent to which students' learning experience has been meaningful and satisfying, and their sentiment on online distance learning due to the implementation of emergency remote teaching (ERT). The study further analyses the causes of Malaysian university students' grievances and challenges and psychological effects in dealing with ERT during the period of the COVID-19 pandemic outbreak and MCO in Malaysia, which prohibited any face-to-face interaction between the period of 18 March 2020 to 30 May 2020. This study employs qualitative methodology in analyzing the content of social media comments following a video post on students' frustration about online distance learning (ODL). Our study provides evidence that ODL, as experienced by the students during the MCO, presented numerous pedagogical, technological, and social challenges which caused a great deal of stress and affects students physically and psychologically. By capturing and analyzing the comments made for a viral video posting of a Malaysian undergraduate student about her personal experience undergoing the ODL, we identify nine factors that contributed adversely to students' learning experience during the ERT period. In more in-depth, we find that the continuous academic assessment tasks, coping with new method of teaching and learning and excessive workload are the main pedagogical challenges. Additionally, technological challenges were present due to lack of reliable internet connection and digital technological equipment and finally, social challenges arise from the lack of family support and understanding, conflicting roles and responsibilities, need for emotional support and unconducive learning environment. Leveraging on the students' experience, we deduced that their encounter with ODL is a reflection of the application of emergency remote teaching (ERT) philosophy.